RESPONS PONDOK PESANTREN AL-HASANAH TERHADAP MODERNISASI DI KABUPATEN BENGKULU TENGAH - Dewi Penghuni (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2020)
This study aims to find out how the response of Al-Hasanah boarding school to the modernization of information communication technology. The nature  of this research  is field research  (qualitative). The source  of this research  data  is the leadership of boarding school Al-Hasanah, teachers  (cleric), board  and  students  of boarding school Al-Hasanah Village Pedati Market District Pondok Kelapa Bengkulu  Tegah  District. The results showed  that modernization at this time can not be sepa- rated  from human life and  in education until the development of Al-Hasanah boarding school changes. However,  as a board- ing school  leader,  teachers  (ustadz),  as well as boarders and  students  of Islamic boarding schools accept  modernization, but modernization accepted by boarding schools is not directly swallowed raw, but Al-Hasanah boarding school is very selective in choosing  the best and  useful for santri for the future. By reason  of seeing the fore for students  who become alumni after being a santri who  plunge  society later. the alumni  can  also enter  the general  high school  after taking education in this pesantren cottage.